The effects of a risk-based approach to tax examinations: Evidence from Tanzania - Amina Ebrahim; Elineema Kisanga; Ezekiel Swema; Vincent Leyaro; Edwin P. Mhede; Ephraim Mdee; Heikki Palviainen; Jukka Pirttilä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
While technical assistance and increased use of ICT in the area of tax administration have been regarded to hold considerable promise for greater revenue collection, the evidence on how these activities work in the real-world circumstances of developing countries is scant. The paper attempts to fill this gap by evaluating an intervention undertaken jointly by the Finnish and Tanzanian revenue administrations. In this pilot programme, a risk-based method for enhancing firm tax examinations in Tanzania was developed. The results, which are based on a difference-indifferences strategy and administrative data from the Tanzanian Revenue Authority, demonstrate that the intervention increased adjusted taxable income by approximately 15 per cent during the first year of the new approach.
Keywords: C93; H26; 330; risk-based approach; firm tax audits; Tanzania